Institutional Anomie, Market-Based Values and Anti-Immigrant Attitudes: A Multilevel Analysis in 28 European Countries - Nickel, Amelie (International journal of conflict and violence, 2022)
Individuals who are strongly oriented towards market-based values are more likely to devalue groups identified as "unprofitable" from an economic point of view. Drawing on insights from Institutional Anomie Theory (IAT), this study explores economically legitimized prejudice in light of a far-reaching economization of the institutional and cultural structure. Multilevel models using data from the European Social Survey (2018) show that hostility towards immigrants is expressed more among individuals who strongly embrace market-based values and in countries where the institutional structure is dominated by the economy and non-economic social institutions are enfeebled (institutional imbalance). Aggregated market-based values (a "marketized anomic culture") mediate the effect of a) individual market-based values and b) institutional imbalance on anti-immigrant attitudes. This study contributes to a better understanding of group prejudice under conditions of economization. It shows that applying IAT within a multilevel framework offers a fruitful explanation not only for crime but for other sociological phenomena.